Tree-ring isotope records of tropical cyclone activity - Miller, Dana L. (National Academy of Sciences, 2006)
The destruction wrought by North Atlantic hurricanes in 2004 and 2005 dramatically emphasizes the need for better understanding of tropical cyclone activity apart from the records provided by meteorological data and historical documentation. We present a 220-year record of oxygen isotope values of α-cellulose in longleaf pine tree rings that preserves anomalously low isotope values in the latewood portion of the ring in years corresponding with known 19th and 20th century landfalling/near-coastal tropical storms and hurricanes. Our results suggest the potential for a tree-ring oxygen isotope proxy record of tropical cyclone occurrence extending back many centuries based on remnant pine wood from protected areas in the southeastern U.S.